Hegel's Encyclopedia of the philosophical sciences: a critical guide - Stein, Sebastian; Wretzel, Joshua (Cambridge University Press, 2021)
Hegel regarded his Enyclopedia of the Philosophical Sciences as the work which most fully presented the scope of his philosophical system and its method. It is somewhat surprising, therefore, that scholars regularly accord it only a secondary status. This Critical Guide seeks to change that, with sixteen newly-written essays from an international group of leading Hegel scholars that shed much-needed light on both the whole and the parts of the Encyclopedia system. Topics include the structure and aim of the Encyclopedia system as a whole, the differences between the greater and lesser Logics, the role of nature in Hegel's thinking, and the shapes of absolute spirit as art, religion, and philosophy. This book will be invaluable to students and scholars with an interest in Hegel and the history of philosophy.
Title from publisher's bibliographic system (viewed on 06 Aug 2021)
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831 -- Encyklopädie der philosophischen Wissenschaften; Hegel, Georg Wilhelm Friedrich / Enzyklopädie der philosophischen Wissenschaften im Grundrisse